In vitro anti-inflammatory activity of 3-O-methyl-flavones isolated from Siegesbeckia glabrescens - Kim, J.Y.; Lim, H.J.; Ryu, J.H.
Four flavones, 3,40-O-dimethylquercetin (1), 3,7-O-dimethylquercetin (2), 3-O-methylquercetin (3)and 3,7,40-O-trimethylquercetin (4)were isolated as the inhibitors of nitric oxide production in activated microglia (IC50 values: 11.1, 4.2, 3.8, and 25.1 lM, respectively). They suppressed the expression of protein and mRNA of inducible nitric oxide synthase. Furthermore, compounds 2 and 3 showed scavenging activity of peroxynitrite with SC50 values of 1.75 and 0.77 lM, respectively.